2013
DOI: 10.3141/2371-01
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Performance of Pavement with High Recycled Asphalt Content

Abstract: This paper summarizes the findings of several case studies on the long-term performance of recycled asphalt pavement (RAP). The goal of these studies was to provide the paving community with documentation on the long-term performance of roadway sections with a high amount of RAP compared with virgin sections on the basis of available information. Roadway sections that contained more than 20% RAP and that had been in place for at least 10 years were identified across the United States with the help of local age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
0
5
0
3
Order By: Relevance
“…The milled asphalt material named reclaimed asphalt pavement (RAP; according to the European norm EN 13108-8) can then be reused by incorporation into a new asphalt mixture, providing possible economic and environmental benefits, as important as the rate of RAP in new asphalt mixtures is high. Anderson and Daniel [1] reported the long-term performance of roadway sections with a high amount of RAP (20 % or more) compared with virgin sections. The results indicated that the sections with high RAP content mainly tended to exhibit a ''lower ride quality, more cracking, and better rutting resistance than the virgin sections, but the differences were not always statistically significant''.…”
Section: Introductionmentioning
confidence: 98%
“…The milled asphalt material named reclaimed asphalt pavement (RAP; according to the European norm EN 13108-8) can then be reused by incorporation into a new asphalt mixture, providing possible economic and environmental benefits, as important as the rate of RAP in new asphalt mixtures is high. Anderson and Daniel [1] reported the long-term performance of roadway sections with a high amount of RAP (20 % or more) compared with virgin sections. The results indicated that the sections with high RAP content mainly tended to exhibit a ''lower ride quality, more cracking, and better rutting resistance than the virgin sections, but the differences were not always statistically significant''.…”
Section: Introductionmentioning
confidence: 98%
“…Great progress has been made in the research of recycled asphalt mixture with a high content of RAP, mainly focusing on the improvement of processing technology, the addition of rejuvenating agents and the assessment of mechanical performance [ 16 , 17 , 18 , 19 , 20 , 21 ]. It is practicable to apply 50% or even more RAP under an optimal condition to meet the requirement of the long-term performance of asphalt pavement in spite of more rutting and crack diseases occurring [ 22 , 23 ]. However, research rarely revealed the environmental impact induced by the application of recycled asphalt mixtures, especially on atmospheric pollution emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for the reluctance to add more RAP to the mix is that RAP contains asphalt binder that has been aged, and incorporating higher RAP contents into HMA can produce mixtures that are stiffer and more brittle than similar mixtures without RAP. Although increased stiffness would improve the rutting resistance of the asphalt mixtures, the reduced ductility makes the mixes more susceptible to thermal and fatigue cracking in the field (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%